From broadcasting to audiovisual: Contributions to the definition of a concept comprehensive in times of media convergence - Napolitano, Carlo José; Leite, Flávia Piva Almeida [UNESP] (Conselho Nacional de Pesquisa e Pos-Graduacao em Direito - CONPEDI, 2020)
Objective: To indicate theoretical contributions of legal documents and of the communication field, national and foreign, to overcome the concept of broadcasting and its expansion to the concept of audiovisual in an environment of media convergence. Methodology: The present paper backed by bibliographic and documentary research uses a deductive analytical-systematic method in order to demonstrate the issues and point out the theoretical, legal and communicational contributions, and of national and foreign documents on the subject. Results: The theory and Portuguese legislation, in addition to the European directives on audiovisual, can contribute to the definition of a broader concept of broadcasting in Brazilian legislation, expanding the concept beyond the electromagnetic spectrum, encompassing any and all broadcasting services, audiovisual media, regardless of technological support. Contributions: A definition and a conceptual clarification, necessary in times of media convergence and internationalization of markets; facts that impact local regulation, changing the configuration of domestic law, as a rule and historically guided by architectural and structural aspects of limitation of the electromagnetic spectrum, which moves towards regulation geared to content.
Da radiodifusão para o audiovisual: Contribuições para a definição de um conceito abrangente em tempos de convergência midiática1
Keywords: Broadcasting; Constitution; Media convergence; Social communication; Television